Study of Microbiological Quality of Fresh Juices Vended in Dhaka City - Afroz, Kayseri; Shammi, Tahmina; Kabir, Md Shahidul (Bangladesh Journal of Microbiology, 2019)
Fresh juices sold by the street vendors are rich in nutritional value and considered as popular drink in Dhaka city .They can be easily contaminated by pathogenic bacteria from unhygienic environment of food preparation area and serves as a potential source of food borne outbreaks. Freshly produced juices of papaya (n = 2), wood apple (n = 2), wood apple and papaya juice (1), lemon (n = 2), and sugarcane (n = 3) were examined for the total bacterial mload, coliforms, Staphylococcus spp., Pseudomonas spp., Vibrio spp., Salmonella spp., and Shigella spp. in this study. Total bacterial load in eight samples were within 0 to 107 cfu/ml, six samples exhibited the presence of staphylococci within the range of 0 to 105 cfu/ml. Total coliforms were detected in six samples which ranged from 104 to 105 cfu/ ml. Vibrio spp., Salmonella spp., and Shigella spp. were isolated by enrichment and selective plating method. Eight samples demonstrated the presence of Vibrio spp. and none of them were positive for Salmonella spp. and Shigella spp. Antibiotic sensitivity patterns were determined against eight isolates using Erythromycin (15μg), Amoxicillin (10 μg), Gentamicin (10 μg), Vancomycin (30 μg), Ciprofloxacin (5 μg), Rifampicin (5 μg), Azithromycin (15 μg), Neomycin (10 μg) and Cefexime (5 μg). Klebsiella sp. (n = 1), Vibrio sp. (n = 2), Enterobacter sp. (n = 1), and Proteus sp. (n = 1) showed multi drug resistance in this study. Contamination of street vended juices pose risks to consumers health and requires adequate attention of appropriate authority. Bangladesh J Microbiol, Volume 36 Number 1 June 2019, pp 49-53